The rural health practice program in Obando, Bulacan an evaluation study - Dungog, Estrella F. 1939-
This is an in-depth evaluation of the impact of the Rural Health Practice Program (RHPP) on the recipients (barrio folks) and deliverers (medical and nursing participants of the program) of health care in two rural fishing barrios. One hundred fifty randomly selected households in Barrio Binuangan and Barrio Salambao and all the five participants to the Ninth batch of the RHPP (4 nurses and 1 physician) in Obando, Bulacan, comprised the subjects of the study. The RHPP had no impact with regard to improvement in health conditions nor did it have any impact on the RHPP participants in terms of improving their attitude toward serving in rural areas and perspective of the socioeconomic development program of the government. However, it strengthened the existing health services and medical manpower in the rural areas.